Leishmania Infection Induces MicroRNA hsa-miR-346 in Human Cell Line-Derived Macrophages - Diotallevi, Aurora; De Santi, Mauro; Buffi, Gloria; Ceccarelli, Marcello; Vitale, Fabrizio; Galluzzi, Luca; Magnani, Mauro (Frontiers in Microbiology, 2018)
Leishmaniasis is an anthropo-zoonotic disease caused by various Leishmania species. The clinical manifestations of the disease vary according to the species and host characteristics. Leishmania infection leads to subversion/modulation of the host’s innate immune response and cellular metabolic pathways. In the last years, it has been shown that many host cell gene expression and signaling pathways are targeted by Leishmania to subvert host defenses (e.g., oxidative damage, immune activation, antigen presentation, apoptosis) and allow parasite survival and replication. However, the molecular mechanisms triggered by the parasite are not fully elucidated. The role of miRNA has recently been evaluated in human or murine macrophages infected with Leishmania (Leishmania) major, L. (L.) donovani or L. (L.) amazonensis. However, no literature exists regarding miRNA dysregulation in host cells infected with L. (L.) infantum or L. (Viannia) species. Since we previously showed that L. (L.) infantum infection induced unfolded protein response (UPR) in macrophages, we focused on miR-346, which has been shown to be induced by the UPR-activated transcription factor sXBP1 and has a potential role in the modulation of the immune response. Macrophages differentiated from U937 and/or THP-1 human monocytic cells were infected with four L. (L.) infantum strain/clinical isolates and one L. (V.) sp. clinical isolate. A significant upregulation of miR-346 (p<0.05) was observed in infections with all the Leishmania species tested. Moreover, RFX1 (a miR-346 predicted target gene) was found to be significantly downregulated (p<0.05) after 48h infection, and miR-346 was found to have a role in this downregulation. The induction of miR-346 in macrophages infected with L. (L.) infantum and L. (V.) sp., reported here for the first time, could play a role in regulating macrophage functions since several MHC- or interferon-associated genes are among the targets of this miRNA. Hence, miR-346 could be considered an attractive anti-Leishmania drug target.